New genes with roles in the C. elegans embryo revealed using RNAi of ovary-enriched ORFeome clones - Fernandez, Anita G.; Gunsalus, Kristin C.; Huang, Jerry; Chuang, Ling-Shiang; Ying, Nancy; Liang, Hsiao-lan; Tang, Caroline; Schetter, Aaron J.; Zegar, Charles; Rual, Jean-François; Hill, David E.; Reinke, Valerie; et al.

(untitled) (Genome Research, 2005)
Several RNA interference (RNAi)-based functional genomic projects have been performed in Caenorhabditis elegans to identify genes required during embryogenesis. These studies have demonstrated that the ovary is enriched for transcripts essential for the first cell divisions. However, comparing RNAi results suggests that many genes involved in embryogenesis have yet to be identified, especially those eliciting partially penetrant phenotypes. To discover additional genes required for C. elegans embryonic development, we tested by RNAi 1123 ORFeome clones selected to represent ovary-enriched genes not associated with an embryonic phenotype. We discovered 155 new ovary-enriched genes with roles during embryogenesis, of which 69% show partial penetrance lethality. Time-lapse microscopy revealed specific phenotypes during early embryogenesis for genes giving rise to high penetrance lethality. Together with previous studies, we now have evidence that 1843 C. elegans genes have roles in embryogenesis, and that many more remain to be found. Using all available RNAi phenotypic data for the ovary-enriched genes, we re-examined the distribution of genes by chromosomal location, functional class, ovary enrichment, and conservation and found that trends are driven almost exclusively by genes eliciting high-penetrance phenotypes. Furthermore, we discovered a striking direct relationship between phylogenetic distribution and the penetrance level of embryonic lethality elicited by RNAi.